(3GdeTGYQ aj GdMceI GdeJYGdjIs - (3GdTjQGRj, GdbhGej, GdeqdG, UOQ GdOjf, eMeO Hf EHQGgje Hf jMji, J (B1059 (3g`s
(3ChdgG (B:s
(3fMeO Gddg hfSJYjf HbhJg (B... (3CjgG GdENhGf GdSGdchf Edi Gddg HfhQ GdYQaGf GSJeYhG HCSeGY bdhHce ebGdJj djfaP aj HhGWfce fhQ MceJj hCWjYhG cdeJj hNPh Yfj efGSc WQjbJj (B...s
(3BNQgG (B:s
... (3GdJj gj ef LhGgQ GdedchJ hef SfN YGed GdLHQhJ eJi JTHgJ HGdeHGOF hGdYdd aj hUaj GdYde hGdYed jaYd CeKGd CaYGdgG hEf cGfJ CVYa (B.. (3hCfRd hgPG cGdMOjO GdMGejI (B... (3aj eYQaI GdQHhHjI(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B5/ 303s
(3GdPQjYI (B21\3838s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs